PENGARUH KUALITAS PRODUK, KETERSEDIAAN PRODUK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK LULUR MANDI SUMBER AYU DI JAKARTA - Charles Victor B. Saragih (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: This study aims to analyze the effect of product quality, product availabilityand lifestyle on purchase decision. Sumber Ayu Body Scrub was taken as a case study.This research is descriptive quantitative in nature. Both primary and secondary datawere employed. Secondary data were taken from various sources such as journals andbooks. Primary data were taken using questionnaire. A total sample of 100 wereobtained. The result shows that purchase decision was influenced by product quality,product availability and life style. The identical result found by previous researchers.Life style was found dominant variabel toward purchase decision.Keywords: Product Quality, Stock Availability, Life Style, Purchase Decision